(3eGFOI GHf LOYGfs - (3eMeO Hf YHO Gddg Hf UdGMjs ((3ehQjJGfjG s)
(3ChdgG (B:s
(3CeG HYO adeG cGf GdYde gh GdWQjb Edi Gddg hgh GdSdGe deMGQHI ef YGOGg dQOJ Cf CUfa eUfakG djS HGdWhjd Gdeed dYSQ NJeg hcJGHJg , hdG HGdbUjQ GdeNd dbdI eSGFdI haGFOJg eTJedkG Ydi eGFI aGFOI s
(3BNQgG (B:s
(3GdTjN SYO jhg HjV Gddg hLgg Hf GdTjN eMeO aGVd Hf GdTjN eCejf Gdbdbei GdMSfi QVi Gddg Yf GdLejY HLGg GdfHi GdTajY s
(3GdfSNI HgG MhGTs
(3HgG JBcd ai HYV LhGfHgGs
(3hYdjgG JUMjMGJ hbjhOGJ hgj fSNI eWGdYIs
(3HgG fXGe GdJYbjHI s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
Keywords: (3Gdabg GdeGdcjs